PROSES PEMBUATAN KRIPIK BUAH NANGKA (Artocarpus heterophyllus) Di CV. SARI AGUNG KECAMATAN GENTENG KABUPATEN BANYUWANGI: The Process of Making Jackfruit Chips at CV. Sari Agung Genteng Banyuwangi - Gabrielia Aling Sucianti Rosiana Ulfa, Bagus Setyawan (JURNAL TEKNOLOGI PANGAN DAN ILMU PERTANIAN (JIPANG), 2021)
Jackfruit chips are chips processed by jackfruit that are fried specially, usually using a vacuum fryer. If using the usual frying method, namely with the skillet, the jackfruit will not turn into chips because the fruit will be damaged by excessive heat. By using a vacuum fryer, the jackfruit is fried at a lower temperature of around 50-60°C so as not to damage the jackfruit. The purpose of this study is to know the process of processing fruit chips at CV. Sari Agung Genteng Banyuwangi. The method used by collecting data through direct observation of the object of observation, namely direct interviews with all related parties, direct practice, and secondary data collection. The results obtained from this study are the packaging of jackfruit chips is done using aliminum foil so that product quality is maintained and during the drying process, the jackfruit is frozen first to maintain the color and texture.